تطبيقات قاعدة الحكم يدور مع علته وجودًا وعدمًا: المعاملات المالية أنموذجًا - Muhammad Said Almujahed; Mohammad Said Titoon Alrashdi (Al-Zahra : Journal for Islamic and Arabic Studies, 2022)
The research is significant because it examines the jurisprudential applications of the maxim "judgement conforms to the existence of the cause, or its absence" in financial transactions. One of the factors that prompted this writing was the difficulty of invoking direct jurisprudential applications of this maxim from classical Fiqh writings, which bequeathed a desire to know the reasons for the emergence of this problem. The problem statement of this research is: does this maxim have applications in the jurisprudential heritage in general and in financial transactions? The research relied on three approaches: the historical approach, as it was resorted to in examining the practical applications of the maxim in financial transactions; the descriptive approach, to write down the contents of this subject and describe them clearly; and the analytical method, to dismantle data and link them to each other.  The research relied on three approaches: the historical approach, as it was resorted to in examining the practical applications of the maxim in financial transactions; the descriptive approach, to write down the contents of this subject and describe them clearly; and the analytical method, to dismantle data and link them to each other. The study differed from earlier studies in that it focused on the application of the maxim in financial transactions, when previous studies did not, because the maxim's applications were limited to the judiciary and witnesses.  In the rooting of the provisions of various financial transactions, jurists relied on the maxim "judgement conforms to the existence of the cause, or its absence," according to the findings. The sale of surplus water, the selling of dead skin, the sale of wine, the sale of paper, the sale of interest, and the sale of interest and money are among the sixteen jurisprudential applications examined in the study. Nine applications are made in the chapters on wills and related applications: will for inheritor, amount of will, interdiction of mentally retarded persons, juvenile and insane persons, time of lifting of interdiction if interdiction is removed and then returned, the reason for establishing pre-emption in movable and immovable property, and pre-emption in the neighbourhood